The Correlation Between Oral Presentation Practice and EFL Students’ Speaking Ability at Islamic State University Raden Mas Said Surakarta - Elisa Dwi Yurianti; Farah Khoirunnisa; Indah Dwi Rahmawati; Wanda Nayla Rahma; Sujito (Jurnal Inovasi Global, 2026)
Speaking ability is one of the fundamental skills for effective communication specifically for EFL (English as a Foreign Language) learners. This study investigated the correlation between oral presentation practice and EFL students’ speaking ability at UIN Raden Mas Said Surakarta. The study aimed to determine whether oral presentation practice is associated with students’ speaking ability in an EFL context. A quantitative correlational design was employed using a survey method. The participants were students of the English Education Department (PBI) at Islamic State University Raden Mas Said Surakarta. Data were collected through a questionnaire measuring students’ oral presentation practice and a speaking test assessing their speaking ability. The data were analyzed using Pearson Product-Moment Correlation. The findings showed that there is a high positive correlation between oral presentation practice and students’ speaking ability. The results indicate that students who frequently engage in oral presentation practice tend to have better speaking ability. Therefore, oral presentation practice can support the development of students’ speaking skills in the EFL classroom.